The Influence of Public Information Disclosure on Transparency and Public Trust in The Batu City Government - Bintang Hapray; Hayat Hayat; Didik Supriyanto (Universitas Islam Darul Ulum Lamongan, 2026)
This study aims to determinate the effect of public information disclosure on transparency and public trust in the Batu City Government. This was done as an effort by the Government to improve transparent and informative governance and to carry out its mandate in accordance with Public Information Disclosure Law Number 14 of 2008, which enables the public to experience a more open system of government. The research method used an explanatory quantitative approach through field research on public information disclosure. The result of the study show that the higher the level of public information disclosure, the higher the level of transparency and public trust in the government, especially in the Batu City Government. The Challenge as a city that was once categorized as an uninformative city in 2023 can be addressed so that in 2024 and 2025, Batu City can receive an award as an informative city that is open to public information needs. Therefore, public information disclosure is a government strategy to realized a transparent government that can be trusted by the public, especially the people of Batu City, whose public information needs can be met by the Batu City Government, which is serious in implementing the mandate of Public Information Disclosure Law Number 14 of 2008.